RG-Homomorphism and Its Properties - Patthanangkoor, Poonchayar (Thai Journal of Science and Technology, 2018)
Abstract In this paper, we investigate RG-homomorphism properties. Moreover, the relations between the quotient RG-algebra and the RG-homomorphism are provided. Keywords: RG-algebra; RG-homomorphism; RG-antihomomorphism; RG-ideal